2017
DOI: 10.1097/rli.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Detection Rate of Simulated Microcalcifications in Full-Field Digital Mammography, Digital Breast Tomosynthesis, and Synthetically Reconstructed 2-Dimensional Images Performed With 2 Different Digital X-ray Mammography Systems

Abstract: In the presented in vitro environment using an anthropomorphic phantom model, standard full-field digital x-ray mammography was superior to synthetically reconstructed 2-dimensional images in the detection of simulated microcalcifications. In view of these results, it is questionable whether Synthetic-2D images can replace FFDM in clinical examinations at the present time. Further investigations are needed to assess the clinical impact of the in vitro results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
16
1
1
Order By: Relevance
“…We found that this also holds true for INSIGHT3D without significant differences with respect to SM or the standard stack reconstruction. Previous studies about SM described a worse depiction of the morphology of microcalcifications compared to FFDM [7,12]. This comparison, however, was not part of this study and describing the morphology with either of these reconstruction techniques might not be comparable with FFDM.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…We found that this also holds true for INSIGHT3D without significant differences with respect to SM or the standard stack reconstruction. Previous studies about SM described a worse depiction of the morphology of microcalcifications compared to FFDM [7,12]. This comparison, however, was not part of this study and describing the morphology with either of these reconstruction techniques might not be comparable with FFDM.…”
Section: Discussioncontrasting
confidence: 43%
“…While the advantages of SM, such as better and faster comparability to previous examinations and contralateral imaging [6], are preserved with INSIGHT3D, its superior depiction of microcalcifications shows added value to SM. In this context, however, it should be remembered that it is not yet clear whether SM can generally substitute FFDM for the depiction of microcalcifications [7,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DBT is now being evaluated as a stand-alone technique for screening in women with dense breasts. The development of synthetic 2D images of comparable quality to standard DM (except for microcalcifications) goes some way to relieve concerns about radiation dosages (190,191) and DBT with either synthetic or standard 2D DM is substantially more sensitive than 2D DM alone (192). Subgroup analysis of the UK TOMMY trial demonstrated that DBT was significantly more sensitive than 2D DM in women with more than 50% MD (93% and 86% respectively, p 0.03) (193).…”
Section: Risk Adapted Screening Protocolsmentioning
confidence: 99%